2017
DOI: 10.1007/s00268-017-4048-x
|View full text |Cite
|
Sign up to set email alerts
|

A Different Kind of Craving: Incidence and Treatment of Pica After Laparoscopic Roux‐en‐Y Gastric Bypass

Abstract: Pica is a rare phenomenon associated with iron deficiency and can occur despite oral iron supplementation. In our experience, intravenous iron can relieve symptoms. Patients considering bariatric surgery should be counseled on pica. Patients with unusual cravings should be evaluated for iron deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Pica—the abnormal craving or pattern of eating nonfood items—is highly suggestive of iron-deficiency anemia 18,19. The most common symptom of pica is pagophagia, or compulsive ice eating 20. A recent study demonstrated that patients with pica after bariatric surgery all had iron deficiency 20…”
Section: Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pica—the abnormal craving or pattern of eating nonfood items—is highly suggestive of iron-deficiency anemia 18,19. The most common symptom of pica is pagophagia, or compulsive ice eating 20. A recent study demonstrated that patients with pica after bariatric surgery all had iron deficiency 20…”
Section: Symptomsmentioning
confidence: 99%
“…18,19 The most common symptom of pica is pagophagia, or compulsive ice eating. 20 A recent study demonstrated that patients with pica after bariatric surgery all had iron defi ciency. 20…”
Section: Symptomsmentioning
confidence: 99%
See 1 more Smart Citation